Improved diffusion and storage of lithium ions via recrystallization induced conducting pathways in a Li:Ta2O5-based electrolyte for all-solid-state electrochromic devices with enhanced performance. (2nd July 2022) - Lin, Chun-Chu; Chen, Po-Hsun; Chen, Min-Chen; Wang, Min-Chuan; Yang, Chih-Cheng; Huang, Hui-Chun; Wu, Chung-Wei; Chou, Sheng-Yao; Tsai, Tsung-Ming; Chang, Ting-Chang
Abstract: In this study, we have investigated the improvements in the performance of an all-solid-state complementary electrochromic device (ECD) by using the proposed high pressure treatment (HPT). The Li:Ta2 O5 electrolyte layer was recrystallized by the HPT utilizing pressurized CO2 gas (∼200 atm) and at low temperature (<60 °C), which enhanced the coloration performance of the WO3 /Li:Ta2 O5 /NiO complementary ECD by ∼20%. The reliability and durability of the ECD were confirmed by long term transmittance retention measurements, which indicated an improvement in the coloration performance by ∼14% upon the release of the bias voltages. The ability of the devices that were fabricated with and without the HPT process to withstand high temperature environments was also verified. In addition, photoluminescence (PL) and transmittance measurements were carried out to examine the effects of the bonding between WO3 and NiO. To determine the differences in lithium-ion (Li + ) injection, electrical measurements were performed by utilizing varying pulse rising speeds to confirm device characteristics. The materials were characterized in terms of their composition and structure using high-resolution transmission electron microscopy along with energy-dispersive x-ray spectroscopy. Finally, a mechanistic model has been proposed to explain the improved EC characteristics based on the amorphous to crystalline transition accompanying the HPT process.